Fractures in CKD Patients-Risk Analysis in RRT Lombardy Patients - Ferruccio Conte; Daniela Paola Roggeri; Mario Gennaro Cozzolino; Carlotta Rossi; Carlo Zocchetti; Alessandro Roggeri (MDPI AG, 2023)
The increase in the number of patients with CKD starting dialysis treatment has become a major health problem in recent years. Osteoporosis is a typical feature of advanced age, which, in the dialysis population, is almost always accompanied by uremic osteodystrophy (CKD-MBD). These two factors are involved in the pathogenesis of fractures, which represent an important risk factor for the outcome of patients. The real consistency of fractures in CKD patients on kidney replacement therapy (KRT) requiring hospitalization in the Lombardy region (over 9,000,000 inhabitants) was analyzed using data from the regional administrative databases in the years 2011-2012. Among 8109 prevalent patients, 251 (45.8% women), with fractures after 1 January 2011, entered the analysis. A follow-up of two years (2011-2012) was considered to evaluate the incidence of more frequent fractures (femur, pelvis, hip, and spine) using ICD-9-CM codes. The most frequent sites of fractures were the femur (68.5%), hip and pelvis (47.4%), and vertebrae (12%). The patients on hemodialysis (HD) had more events than PD (3.3% vs. 1.4%; p = 0.03), while patients undergoing kidney transplantation (KTx) had a significantly lower percentage of fractures (0.6% vs. 3.3%; p < 0.001). Observed mortality was very high: the estimated gross mortality rate for any cause was 25.9% at 90 days and 34.7% at 180 days. Diabetes, peripheral vasculopathy, and heart failure were associated with a numerical increase in fractures, although this was not significant. Proton pump inhibitor drugs (PPI), vitamin K antagonists, and diphosphonates were more frequently associated with fracture occurrence. The average total cost of fractured patients was 11.4% higher than that of non-fractured patients. On multivariate analysis, age >65 years, female gender, PPI therapy, and cerebrovascular disease were found to be strongly associated with fractures in dialysis patients, whereas undergoing renal transplantation presented a reduced risk.